PENGEMBANGAN AYAM HIBRIDA DALAM RANGKA MENDUKUNG SWASEMBADA DAGING DI JAWA TENGAH - Sriyanto Sriyanto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2013)
Agricultural development aims to achieve sustainable industrial agriculture, based on local resources, food self-sufficiency and well-being of farmers. Consumption of animal food is not just resting on red meat (beef ), so that the chicken is not race plays an important role, but the level of consumption is still low ( 7 kg / capita / year ) , and has not been a priority, traditionally maintained as a sideline. The aim of this study is to describe the development policies of poultry ( chicken free-range / hybrid ), the development and deployment of technological innovations Artificial Insemination ; cultivation of hybrid chickens and chicken hybrid models for sustaining economic self-sufficiency of families and meat. The results of this study is that the poultry development policy (domestic poultry/ hybrid ) has not been a priority. High domestic poultry population (13.83 % of national) ; development and deployment of technological innovation has spread chicken Artificial Insemination developed by farmers on a limited scale. The role of government is not optimal . Hatching effort with limited capacity, because breeders are limited , cooperation with farmer laying hens is not easy to do. Raising chickens has not been widely cultivated hybrids by the surrounding community. Hybrid model of chicken farming by empowering farmers, ranchers target domestic poultry in the village, with the village as a center scale "village chicken hybrids" ; main partners are manufacturers of hybrid nearest DOC chicken and chicken vendors, and poultry. Model-scale centers to be efficient, mutually reinforcing, profitable, sustainable and shorten the marketing chain . Institute of Livestock need to establish pilot programs to empower farmers in a village "village chicken hybrid" embryos as agribusiness cluster models (pilot unit independent business not a sideline), side by side with free-range chicken farming .